Physiological conditioning evolution during the season of Atletico Madrid B women soccer team - Calleja, J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
During the last years, scientific studies have shown a descriptive analysis of physiological (Tamer et al. 1997) and morphological characteristics (Can, Yilmaz & Erden, 2004) of elite soccer women players, during specific periods of training (Jensen & Larsson, 1998). But there is not scientific evidence with medium level women players during a regular season. Thus, the purpose of this investigation was to evaluate the performance of the players of Atletico Madrid B women`s team during the 2005/2006 season and to value is it possible the modification and evolution throughout the season as a result of the training process. Materials and Methods. Twelve female players (mean± sd; age=16.6±124 yr; weight=577±9.6 kg; height=1.60±0.06 cm) volunteered for this study. Body Mass Index (BMI) and percentage of body fat was measured by Faulkner ecuation( 4). Test items included agility (Test de Barow), speed (10 m, 20 m , 30 m), flexibility (Sit & Reach) and strength (Abalakov test and Countermovement jump test) during three different moments of the season: preparatory period, competitive period and transitory period. Results. A significant change in the values of BMI nor in the percentage of corporal fat throughout season was not observed. The statistical analysis showed the progressive improvement in the performance of the players in all the test made except in the speed test (10 m). Conclusion. The main finding of our study described the progressive improvement in the performance of all the capacities but the BMI and the corporal fat not presented significant changes during the season.